Determination of Institutional and Individual Factors for the Implementation of the Merdeka Belajar Kampus Merdeka - Rahmawati, Rukhaini Fitri; Maghfirah, Nuril (Al-Hayat: Journal of Islamic Education, 2025)
This study analyzes the multifaceted relationship between institutional and personal determinants that mold the execution of the Merdeka Belajar Kampus Merdeka (MBKM) program at the Faculty of Da'wah and Communication in particular State Islamic Universities (PTKIN) in Central Java and Yogyakarta. The analysis seeks to chart strategic priorities for implementing MBKM in the religious higher education setting. This research uses a qualitative descriptive field study approach. Data were collected through semi-structured interviews, non-participant observations, and document reviews from purposively selected informants like faculty heads, lecturers, students, and external partners. The data were evaluated using the Miles and Huberman interactive model, supported by triangulation, member checking, and peer debriefing to ensure validity. The study finds that successful MBKM execution is greatly influenced by strategic interunit communication, adaptive organizational structure, and incorporation into existing academic systems. Conversely, key inhibiting elements include bureaucratic rigidity, nonstandardized assessment processes, limited socialization, budgetary constraints, and weak external collaboration. These dynamics reflect the practical application of Pressman & Wildavsky's policy implementation theory, Mazmanian & Sabatier's structural framework, and Lewin's Unfreeze–Change–Refreeze model, demonstrating that effective policy adoption necessitates structural transformation and cultural adaptation. This research is exploratory and context-specific, focusing on selected PTKIN in Central Java and DI Yogyakarta. It does not include longitudinal data or viewpoints from alums and national-level stakeholders, restricting its generalizability. This study contributes to the literature by offering an in-depth policy analysis of MBKM implementation in religious higher education institutions using a combination of classic policy implementation and organizational change theories—an approach infrequently used in previous research in this domain.